Urgensi Pendidikan Akhlak pada Anak Usia Dini Menurut Perpsektif Psikologi Islam - Khairunnisa, Indah; Diponegoro, Ahmad Muhammad (DAYAH: Journal of Islamic Education, 2024)
The background of this research is the importance of strengthening moral education in early childhood. Given that early childhood is a child who is in the golden age, the moral education provided is the basis for the development of children's morals. This study aims to analyze the role and methods of moral education in early childhood according to the perspective of Islamic psychology. This research method uses library research, where research data is obtained from literature sources. The results in this study indicate that there are several methods of moral education that are in accordance with the development of early childhood according to Islamic psychology, namely exemplary methods, playing and telling stories, reward and punishment, and habituation.